PERLINDUNGAN HUKUM TERHADAP NASABAH PENGGUNA ATM SETOR TUNAI PADA BANK NEGARA INDONESIA (BNI) CABANG PASAR BAWAH PEKANBARU - Yarmalis, Yogi; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The use of ATMs as a facility to make it easier for customers to make cashwithdrawals with banks has changed the banking transaction process from conventionalto virtual in nature where parties do not meet in person but simply through electronicmedia. The use of ATMs, which provide various banking transactions is simpler andfaster, however in fact the use of ATMs can cause problems in usage for customers.This type of legal research is sociological legal research, which in this research, iscarried out directly into the field to collect primary data, and uses descriptive methods.Meanwhile, if viewed from the nature of this research is descriptive.The results of this study are the losses experienced by customers in carrying outcash deposit transactions at BNI ATMs Pasar Bawah Pekanbaru branch which areproblematic are material and immaterial losses. Material loss because the customer hasnot received compensation for lost money due to a malfunctioning cash deposit ATM.The immaterial loss suffered by the customer is that a lot of time is wasted in handlingthe complaints procedure to the bank. The responsibility of BNI Bank, Pasar Bawah,Pekanbaru branch for losses suffered by customers in carrying out cash deposittransactions at problematic ATMs is still not maximized, such as settlement times thatare not in accordance with SOPs. The bank only accepts customer complaint reportsand is still being processed. For compensation, the bank has not yet realized it becauseit is still in the process of settlement.Keywords: Legal Protection, Customers, ATM